Analisis Kelayakan Finansial Padi Ladang di Kabupaten Buton Utara (Studi Kasus di Desa Ronta Kecamatan Bonegunu Kabupaten Buton Utara) - Zakariah, Agista Auliani Istiqfarah; Abdi, Abdi; Yusria, Wa Ode (Department of Agribusiness, Halu Oleo University, 2021)
This study aims to determine the financial feasibility of upland rice farming in Ronta Village, Bonegunu District, North Buton Regency. The research was carried out in May 2021 - June 2021 in Ronta Village, Bonegunu District, North Buton Regency. The research data were analyzed using quantitative methods with cost, revenue, income, and financial feasibility. The study results showed that upland rice farming in Ronta Village, Bonegunu District, North Buton Regency was feasible to cultivate and develop based on economic feasibility criteria. The NPV value obtained was IDR 958.8 with an interest rate of 14%, BEP IDR 4,614, and 72.78 kg. IRR is 25%, the required Payback Period is 1.5 years, and the B/C Ratio is 3.76. In the sensitivity analysis, if there is a 30% decrease in price, then the upland rice farming in Ronta Village is not feasible to develop because it does not meet the five financial feasibility investment criteria.